Psychological determinants of burnout, illness and injury among elite junior athletes - Moen, F.; Myhre, K.; Sandbakk, O. (The Sport Journal, 2016)
This article looks at how psychological variables such as passion, perceived performance, affect, worries and working alliance are associated with athlete burnout and illness and injuries among junior athletes in sport. A sample of 356 junior elite athletes from different sports such as cross country skiing, biathlon, Nordic combined, shooting, ice-hockey, ice-skating, ski jumping, alpine skiing, cycling, track and field, football, orienteering, handball, football and volleyball participated in the investigation. Our results show that harmonic passion, perceived performance, positive and negative affect, worry and working alliance are uniquely associated with athlete burnout, whereas sex, perceived performance and working alliance uniquely are associated with illness and injuries. The results are discussed in regard of applied implications and possible future research.